Condicionamento estrutural das zonas de cisalhamento da região de Forquilha, domínio Ceará Central: uma abordagem integrada de sensoriamento remoto e geologia estrutural - Cunha, Fábio Souza e Silva da (2007)
The studied region, named Forquilha and localized in northwestern Central Ceará domain (northern portion of Borborema Province), presents a lithostratigraphic framework constituted by paleoproterozoic metaplutonics, metasedimentary sequences and neoproterozoic granitoids. The metasedimentary rocks of Ceará group occupy most part of the area. This group is subdivided in two distinct units: Canindé and Independência. Canindé unit is represented basically by biotite paragneisses and muscovite paragneisses, with minor metabasic rocks (amphibolite lens). Independência sequence is composed by garnetiferous paragneisses, sillimanite-garnet-quartz-muscovite schists and quartz-muscovite schists, pure or muscovite quartzites and rare marbles. At least three ductile deformation events were recognized in both units of Ceará group, named D1, D2 and D3. The former one is interpreted as related to a low angle tangential tectonics which mass transport is southward. D2 event is marked by the development of close/isoclinal folds with a N-S oriented axis. Refolding patterns generated by F1 and F2 superposition are found in several places. The latest event (D3) corresponds to a transcurrent tectonics, which led to development of mega-folds and several shear zones, under a transpressional regime. The mapped shear zones are Humberto Monte (ZCHM), Poço Cercado (ZCPC) and Forquilha (ZCF). Digital image processing of enhanced Landsat 7-ETM+ satellite images, combined with field data, demonstrate that these penetrative structures are associated with positive and negative geomorphologic patterns, distributed in linear and curvilinear arrangements with tonal banding, corresponding to the ductile fabric and to crests. Diverse color composites were tested and RGB-531 and RGB-752 provided the best results for lineament analysis of the most prominent shear zones. Spatial filtering techniques (3x3 and 5x5 filters) were also used and the application of Prewitt filters generated the best products. The integrated analysis of morphological and textural aspects from filtered images, variation of tonalities related to the distribution of geologic units in color composites and the superposition over a digital elevation model, contributed to a characterization of the structural framework of the study area. Kinematic compatibility of ZCHM, ZCPC, ZCF shear zones, as well as Sobral-Pedro II (ZCSPII) shear zone, situated to the west of the study area, was one of the goal of this work. Two of these shear zones (ZCHM, ZCPC) display sinistral movements, while the others (ZCSPII, ZCF) exhibit dextral kinematics. 40Ar/39Ar ages obtained in this thesis for ZCSPII and ZCPC, associated with other 40Ar/39Ar data of adjacent areas, indicate that all these shear zones are related to Brasiliano orogeny. The trend of the structures, the opposite shear senses and the similar metamorphic conditions are fitted in a model based on the development of conjugate shear zones in an unconfined transpression area. A WNW-ESE bulk shortening direction is infered. The geometry and kinematic of the studied structures suggest that shortening was largely accommodated by lateral extrusion, with only minor amounts of vertical stretch